Teaching support material: Diagnostic procedures of the nervous system - Companioni, Reyes; Elisa, Martha; Domínguez, Lenia Rubio (Seven Editora, 2024)
Diagnostic procedures are vital tools that help doctors confirm or rule out the presence of a neurological disorder or other disease. Scientific Problem: Insufficient bibliographies, most of which are obsolete Motivation: The dizzying development of technology is not yet within the reach of all students. Material: Data were collected from scattered bibliographies and compiled. Method: analysis and synthesis, once the procedures have been studied, it is possible to synthesize them for a better understanding of the students. Objective: To provide support material to students as a bibliography in programs that require it. DOI:https://doi.org/10.56238/sevened2023.007-093